School attendance among preschool children of diverse backgrounds and teachers’ collaboration with parents during the COVID-19 pandemic - Einarsdóttir, Jóhanna; Rúnarsdóttir, Eyrún María (Menntavísindasvið Háskóla Íslands, 2021)
In the first wave of the COVID-19 pandemic in March 2020, the Icelandic authorities responded to the public health threat by imposing restrictions, including a ban on gatherings of more than 20 people. Such restrictions required school administrators to adapt the operations and practices of their schools to the new reality. In preschools, the standard practice involved inviting children to attend preschool part-time, either on fewer days of the week or for fewer hours in the day. Albeit necessary, temporary school closures disrupt the lives of children and their families and can adversely affect their education, well-being and social relations, especially regarding children in vulnerable groups in society.The benefits of quality preschool education are indisputable. Preschools play a pivotal role in Icelandic society, where they are regarded as part of the education system and where children spend most days with their peers and educators. Preschools are particularly important for children of foreign background, and because immigration into Iceland has risen in the past few decades, preschools there have become more culturally diverse. In general, preschools are often the first stop for families arriving in new countries and sometimes referred to as the windows into their new societies. In turn, quality preschool education emphasising the strengths and experiences of children and collaboration with their families can be crucial in creating equity for children of foreign origin.The study presented here had the aim of providing insight into the school attendance of preschool children of diverse language and cultural backgrounds, as well as into the cooperation of preschool staff with parents during the COVID-19 pandemic. The study used data from a questionnaire survey conducted by the Educational Research Institute in the School of Education at the University of Iceland in June 2020 and a focus group study conducted in August and September 2020 — that is, when the first wave of COVID-19 had passed. The ...